Darman Moenir’s Life and Works: Reflections of Minangkabau Cultural Identity in Indonesian Literature (1970–2012) - Utari, Septa Dwi; Syafrizal, Syafrizal (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
This study explores the life and literary contributions of Darman Moenir, a prominent writer from West Sumatra whose works reflect the interplay between Minangkabau cultural identity and Indonesian literary modernity. The research aims to examine how his personal experiences, socio-cultural background, and artistic vision shaped his writings and career trajectory from 1970 to 2012. Using the historical method, which comprises heuristic, critical, interpretative, and historiographical stages, this study analyzes primary sources, including interviews and personal documents, as well as secondary literary materials. The findings reveal that Darman Moenir's works, including Bako, Dendang, and Aku, Keluargaku, Tetanggaku, embody realism, romanticism, and expressionism while addressing social and cultural themes. His achievements and awards highlight his significant contributions to advancing Indonesian literature. The study concludes that Darman Moenir's life and oeuvre represent an enduring dialogue between local wisdom and national literary expression.